The Role of Intestinal Microbiota in Acute Graft-versus-Host Disease - Yuanyuan Chen; Ye Zhao; Qiao Cheng; Depei Wu; Haiyan Liu (Journal of Immunology Research)
The mammalian intestinal microbiota is a complex ecosystem that plays an important role in host immune responses. Recent studies have demonstrated that alterations in intestinal microbiota composition are linked to multiple inflammatory diseases in humans, including acute graft-versus-host disease (aGVHD). aGVHD is one of the major obstacles in allogeneic hematopoietic stem cell transplantation (allo-HSCT), characterized by tissue damage in the gastrointestinal (GI) tract, liver, lung, and skin. Here, we review the current understanding of the role of intestinal microbiota in the control of immune responses during aGVHD. Additionally, the possibility of using probiotic strains for potential treatment or prevention of aGVHD will be discussed.